Factors associated with adherence to guideline-recommended cardiovascular disease prevention among HIV clinicians. Issue 1 (16th September 2021) - Galaviz, Karla I; Colasanti, Jonathan A; Kalokhe, Ameeta S; Ali, Mohammed K; Ofotokun, Igho; Fernandez, Alicia
Abstract: Integrating cardiovascular disease (CVD) prevention in routine HIV care remains a challenge. This study aimed to identify factors associated with adherence to guideline-recommended CVD preventive practices among HIV clinicians. Clinicians from eight HIV clinics in Atlanta were invited to complete an online survey. The survey was informed by the Consolidated Framework for Implementation Research and assessed the following: clinician CVD risk screening and advice frequency (never to always), individual characteristics (clinician beliefs, self-efficacy, and motivation), inner setting factors (clinic culture, learning climate, leadership engagement, and resources available), and outer setting factors (peer pressure and patient needs). Bivariate correlations examined associations between these factors and guideline adherence. Thirty-eight clinicians completed the survey (82% women, mean age 42 years, 50% infectious disease physicians). For risk screening, clinicians always check patient blood pressure (median score 7.0/7), while they usually ask about smoking or check their blood glucose (median score 6.0/7). For advice provision, clinicians usually recommend quitting smoking, controlling cholesterol or controlling blood pressure (median score 6.0/7), while they often recommend controlling blood glucose, losing weight, or improving diet/physical activity (median score 5.5/7). Clinician beliefs, motivation and self-efficacy were positively correlated with screening and advice practices ( r = .55−.84), while inner setting factors negatively correlated with lifestyle-related screening and advice practices ( r = −.51 to −.76). Peer pressure was positively correlated with screening and advice practices ( r = .57–.89). Clinician psychosocial characteristics and perceived peer pressure positively influence adherence to guideline-recommended CVD preventive practices. These correlates along with leadership engagement could be targeted with proven implementation strategies.